New Product Line Creation and Line Stop Resolution Method Using Lean Principles (The Indonesian Journal of Business Administration, 2021)
"As Indonesia’s industrial sector continues to grow rapidly, Solutions from Power Services business ensure that your gas turbine can fulfil its full lifetime potential, anywhere in the world. Gas turbine component is one of the supporting units of the power plants, PT XYZ is company that focused on repairing B and E class (Frame 3/5/6/7/9) gas turbine. In the end of 2020 PT XYZ stated to become B&E gas turbine service center COE (Center of Excellence) because the increment of capability repair service. It has capability to repair all component of GE gas turbine B/E Class included: Power Nozzle, Liner, Transition Piece, Flow Sleeve, Shroud, Bearing, Bucket. Growing of PT XYZ is impacted to the production capacity, by using lean principle PT XYZ increasing the production capacity on creating new production line. The new production line should be fulfilling the customer demand on 2021. New production line was calculated become the solution of the low production capacity. Based on the takt time, cycle time calculation 11 operators identify as the total manpower need to support the production line. Maximum capacity for the line is 9,954 pcs/year. The maximum capacity meets with 2021 forecast demand as a target on capacity increment, the target of capacity is 7047 pcs/year.Keyword: Lean, Gas Turbine, manpower, cycle time, takt time, new production line, production capacity, new line creation."